Deinde centum: from Catullus to Horace in Janus Secundus’ Basium 16 (Minerva, 2019)
As pointed out by Gregor Vogt-Spira, Catullus’ influence, although an essential aspect in the overall development of Renaissance poetry in Latin, adopts a very radical and remarkable form in Janus Secundus’ Kisses. Thanks to the aesthetic inventiveness of that work, the kiss would become a central object in Renaissance poetry. As Secundus himself became a respected model for imitatio, his Basia spread all throughout Europe and were reprised and translated by the greatest amongst vernacular poets. Our analysis of ‘Basium XVI’ endeavours to show how much of Secundus’ reshaping of Catullian influence undergoes through an extremely careful work on Horatian metrics and themes.
Keywords: Janus Secundus; Catullus; Horace; Neo-Latin Literature; Transmission of Ancient Texts